Parties and democracy in France : parties under presidentialism - Bell, David Scott, 1947- 1947- (Routledge revivals, 2018)
Cover -- Half Title -- Title -- Copyright -- Contents -- Acknowledgements -- Abbreviations and Acronyms -- Introduction: Fourth Republic to Fifth Republic: 'aller-retour'? -- 1 The Impact of the Presidency -- 2 Party System Fragmentation -- 3 Rassemblement pour la République: A Presidential Party -- 4 Union pour la Démocratie Française: The Endurance of the Temporary -- 5 Centre Politics: Force Démocrate - French Christian Democracy,'Libéralisme' - Démocratie Libérate, and the Radical Party -- 6 Front National: Renovation of the Extreme Right -- 7 French Communism: The Patriotic Reflex -- 8 French Socialism: Between Gradualism and the Great Leap Forward -- Conclusion: Parties and Presidential Democracy -- Appendix I The 1997 French General Elections -- Appendix II The RPR -- Appendix III A Note on UDF (Union pour la Démocratie Française) Structure in 1996 -- References -- Further Reading -- Index